ANALISIS METODE PENAFSIRAN HAKIM TENTANG PERKAWINAN BEDA AGAMA (Studi Kasus Penetapan No. 959/Pdt.P/2020/PN.Bdg dan Penetapan No.71/Pdt.P/2017/PN Bla) - Diana Farid; Hendriana Hendriana; Muhammad Husni Abdulah Pakarti (LPPM STAI Muhammadiyah Probolinggo, 2022)
This article discusses the interpretation method used by judges in deciding interfaith marriages. Law No. 19 of 2019 concerning amendments to Law No. 1 of 1974 concerning marriage, interfaith marriages are not explicitly regulated while the Compilation of Islamic Law prohibits the practice of interfaith marriages, resulting in legal disharmony, and the determination of interfaith marriages becomes the subjectivity of judges in determining interfaith marriage. This study aims to determine what interpretation method is used by the judge. The research method used is a qualitative research (library research) with a normative legal approach. The results showed that the determination of no. 959/Pdt.P/2020/PN Regarding interfaith marriages that are granted using a letterlijk interpretation. The judge who refused in the determination of no. 71/Pdt.P/2017/PN Bla uses a holistic interpretive approach.